(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This study examines the application of literary psychologism in the works of Muriel Spark, focusing on how Spark portrays the inner lives and motivations of her characters. Spark’s novels, known for their psychological depth and satirical style, offer nuanced explorations of human nature and consciousness. Through close analysis of key works such as “The Prime of Miss Jean Brodie,” “Memento Mori,” “The Driver’s Seat,” “Loitering with Intent,” and “Aiding and Abetting,” this paper elucidates Spark’s adept use of literary techniques to delve into themes of control, mortality, psychological breakdown, creativity, and identity. By employing literary psychologism, Spark provides profound insights into the complexities of human psychology and the existential dilemmas faced by her characters.